ASISTENSI P5 SMA SINAR DHARMA DENGAN TEMA AUGMENTED REALITY - Carisha Puspa Gozali; Tiga Wira Prasidya; Darius Andana Haris (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Advanced technology has implemented many things, such as entertainment, health, and education. The birth of various innovations is motivated by the development of technology in this ongoing era. One of the technological developments that is quite influential is Augmented Reality, a technology that combines two-dimensional or three-dimensional virtual differences into a real environment. In connection with the government's policy regarding a program called the Pancasila Student Profile Strengthening Project or P5 with the theme